Intraventricular pressure gradient: A novel tool to assess the post-infarction chronic congestive heart failure - El-Husseiny, Hussein M.; Mady, Eman A.; Ma, Danfu; Hamabe, Lina; Takahashi, Ken; Tanaka, Ryou (Frontiers in Cardiovascular Medicine, 2022)
Congestive heart failure (CHF), the leading cause of death, is deemed a grave sequel of myocardial infarction (MI). The employment of left ventricular end-diastolic pressure (LVEDP) as a primary indication of CHF becomes restricted owing to the potential impairment of heart function and caused injury to the aortic valve during measurement. Echocardiography is the standard technique to detect cardiac dysfunction. However, it exhibits a low capacity to predict the progression of CHF post chronic MI. Being extremely sensitive, non-invasive, and preload-independent, intraventricular pressure gradient (IVPG) was lately introduced to evaluate cardiac function, specifically during cardiomyopathy. Yet, the utility of its use to assess the CHF progression after chronic MI was not investigated. Herein, in the current research, we aimed to study the efficacy of IVPG in the assessment of the cardiac function in a chronic MI rat model with CHF and evaluation of its ability to foresee these alterations. Fifty healthy male rats were involved, and MI was surgically induced in 35 of them. Six months post-surgery, all animals were examined using transthoracic conventional and color M-mode echocardiography (CMME) for IVPG. Animals were euthanized the following day after hemodynamics recording. Gross pathological and histological evaluations were performed. J-tree cluster analysis was conducted relying on ten echocardiographic parameters suggestive of CHF. Animals were merged into two main clusters; CHF+ (MI/HF+ group, n=22), and CHF- (n=28) that was joined from Sham (n=15), and MI/HF- (n=13) groups. MI/HF+ group showed the most severe echocardiographic, hemodynamic, anatomic, and histologic alterations. There was no significant change in the total IVPG among various groups. However, the basal IVPG was significantly increased in MI/HF+ group compared to the other groups. The remaining IVPG measures were considerably increased in the MI/HF+ group than in the Sham one. The segmental IVPG measures were significantly correlated with the anatomical, histological, echocardiographic, and hemodynamic findings except for the heart rate. Moreover, they were significant predictors of CHF following long standing MI. Conclusively, IVPG obtained from CMME is a substantially promising non-invasive tool with a high ability to detect and predict the progression of CHF following chronic MI compared to conventional echocardiography.